‘Stop flexing your roots, man’: Reconversion strategies, consecrated heretics and the violence of UK first-wave punk - Branch, Andrew (Punk & post-punk, 2014)
The article assesses how the reshaping of the habitus of UK punk’s original working-class and lower-middle-class practitioners framed their investment in this heavily mediated popular music culture. A reshaping that facilitated an increased reflexivity in these more socially mobile subjects. This is achieved by drawing on both published testimonies and the author’s own empirical research into how former first-wave punks now read their earlier practice. In recognizing first-wave punk’s initial status as a heterodox cultural formation, discursively defined by the modernist aesthetic it laid claim to and by the violence attributed to it in media representations, the article examines the degree to which its practitioners challenged orthodoxy in their desire to consecrate a new field of cultural practice, with its attendant forms of capital. By drawing on a Bourdieusian conceptual framework, the article demonstrates how first-wave punk derived its affective energy from working-class cultures and predicated this modernist aesthetic on the symbolic value it selectively extracted from them. In undertaking such an account, the article suggests that the violence of first-wave punk, symbolic and physical in form, was symptomatic of the divergent classed habitus of its practitioners. It concludes by arguing that in this respect, punk’s opening up of radical space might be read in a more ambivalent light than has hitherto been the case.